Interaction of the apolipoprotein E receptors low density lipoprotein receptorrelated protein and sorLA/LR11 - Spoelgen, Robert (2008)
In this study, we examined protein-protein interactions between two neuronal receptors, low density lipoprotein receptor-related protein (LRP) and sorLA/LR11, and found that these receptors interact, as indicated by three independent lines of evidence: co-immunoprecipitation experiments, surface plasmon resonance analysis, and fluorescence lifetime imaging microscopy (FLIM). Immunocytochemistry experiments revealed widespread co-localization of LRP and sorLA within perinuclear compartments of neurons, while FLIM analysis showed that LRP-sorLA interactions take place within a subset of these compartments.